ANALISIS STRATEGI GURU DALAM MENGEMBANGKAN RANAH AFEKTIF PESERTA DIDIK DI SEKOLAH DASAR - Hasanah, Nurhandayani; Darwisa, Darwisa; Zuhriyah, Indah Aminatuz (Academy of Education Journal, 2023)
In developing attitude assessments in primary schools, a teacher needs to implement effective strategies. Teachers can use a variety of observation techniques on a regular basis to observe student behavior in the classroom context and activities outside the classroom. Teachers can also engage students in self-reflection and peer assessment to gain a more holistic understanding of their attitudes. The method used uses literature study research, where researchers obtain information through documents such as journals, books, and other literature reviews. The result of this study is that by analyzing in-depth, the affective realm refers to one of three domains in Bloom's taxonomy known as Bloom's Revised Taxonomy. This field deals with aspects of emotions, attitudes, and values in learning. A teacher needs to use a variety of strategies that involve creating a supportive environment, setting a positive example, integrating values in teaching, providing time and space for reflection and discussion.